2012
DOI: 10.1259/bjr/42420290
|View full text |Cite
|
Sign up to set email alerts
|

Imaging assessment of desmoid tumours in familial adenomatous polyposis: is state-of-the-art 1.5 T MRI better than 64-MDCT?

Abstract: MRI is at least equivalent (and may be superior) to MDCT for the detection of desmoid tumours in FAP. Coupled with the advantage of avoiding radiation, it should be considered as the primary imaging modality for young FAP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 17 publications
(26 reference statements)
0
21
0
Order By: Relevance
“…DTs can be diagnosed at all ages, but the peak incidence is after the third decade, with 80% of diagnoses made before 40 years of age (21). The incidence of DTs in FAp is 800-to 1,000-fold higher than in the general population (22): DTs occur in between 10% (23) and 15% of patients with FAp (6).…”
Section: Epidemiologymentioning
confidence: 99%
“…DTs can be diagnosed at all ages, but the peak incidence is after the third decade, with 80% of diagnoses made before 40 years of age (21). The incidence of DTs in FAp is 800-to 1,000-fold higher than in the general population (22): DTs occur in between 10% (23) and 15% of patients with FAp (6).…”
Section: Epidemiologymentioning
confidence: 99%
“…Some remain stable for long periods and spontaneous regression has been reported, but many demonstrate locally aggressive behavior with a propensity to recur even after complete resection (46). About 10% show a pattern of relentless growth with marked morbidity and even mortality (59,62). Risk factors for worse prognosis include tumor size larger than 10 cm, extensive involvement of the small bowel, and bilateral hydronephrosis (54).…”
Section: Mesenteric Fibromatosismentioning
confidence: 99%
“… have previously reported that mesenteric desmoid tumours were far more likely to be poorly defined than musculoskeletal desmoids on CT. Sinha et al . have reported that MRI is equivalent to CT for the detection of intra‐abdominal and extra‐abdominal fibromatoses in FAP and may be particularly appropriate for young patients with the advantage of avoiding radiation. On the other hand, MRI has been stated as the imaging of choice for truncal and extremity fibromatoses as they demonstrate low signal intensity on T1 sequences compared with muscle and hyperintense signal (more than muscle) on T2‐weighted images .…”
Section: Discussionmentioning
confidence: 99%
“…CT scan is the imaging modality of choice for cancer recurrence surveillance as in the five cases presented in this series. Brooks et al [38] have previously reported that mesenteric desmoid tumours were far more likely to be poorly defined than musculoskeletal desmoids on CT. Sinha et al [39] have E Two mesenteric deposits likely to be malignant, one 11 mm below the left renal vessels in the small bowel mesentery and a second in the descending colon…”
Section: Discussionmentioning
confidence: 99%